Eating habits and food knowledge in a sample of portuguese university students - Guiné, Raquel (2020)
The choice to adopt a healthy diet is complex, since food choices and eating behaviours are influenced by various factors, such as biological, social, environmental, demographic and psychological aspects. The transition from secondary school to university is a critical period that involves many social and physical environmental changes, which may lead to an unhealthy lifestyle. This study investigated the eating habits, food knowledge and the level of information about a healthy diet in a sample of 670 university students in Portugal. In general, the participants had a good food knowledge and satisfactory eating habits, as well as a satisfactory level of information about a healthy diet. There were found significant differences in the participants’ food knowledge among age groups and according to the area of studies. Most of the students revealed satisfactory eating habits, with significant differences between age groups, the area of studies and the practice of high competition sport. The results pointed to the necessity of improving educational programs which can contribute to increase university students’ food knowledge and consequently improve their eating habits.